Bentuk-bentuk Kesalahan Tanda Baca dan Ejaan dalam Karangan Siswa Kelas IV SD Negeri 1 Demak Ijo - Cintya Mayawati; Gunawan Budi Santoso; Bayu Purbha Sakti (Lembaga Pengembangan Kinerja Dosen, 2024)
The background for choosing the title above is because Enhanced Spelling (EYD) cannot be simply ignored in scientific writing. In other words, the use of punctuation plays an important role in making scientific written language effective for readers. The problem that will be analyzed in this research is how errors are made by writers of capital letters and punctuation in descriptive essays by fourth grade students at SD N I Demakijo? What are the forms of spelling errors in descriptive essays for fourth grade students at SD N I Demakijo.The aim to be achieved is to find out errors in writing capital letters and punctuation in descriptive essays for fourth grade students at SD Negeri I DemakIjo, to describe the forms of spelling errors in descriptive essays for fourth grade students at SD Negeri I DemakIjo.The method used in this research is qualitative method.The research variables are forms of punctuation and spelling errors in the essays of class IV students at SD N I Demakijo. The data in this research consist of errors in the use of punctuation marks in students' essays which are the object of research. The data source in this research is the sample. The research determined the data source in this research, namely student essays made by class IV students at SD Negeri I Demakijo. The data collection technique in this research uses reading and note-taking techniques. Data analysis uses qualitative descriptive analysis. From the results of the analysis, it was found that types of language errors included a) errors in writing full stops, b) errors in writing commas, c) errors in writing hyphens, d) errors in capital letters. A form of spelling error is an error in using a period which is caused by the writer not including a period at the end of the sentence. The second form of error, namely errors in using commas, is caused by several factors, for example, in a detail or number, commas are not found between the elements. The third form of error is the use of hyphens because they were not included in the student's essay. The last form of error is a capital letter error which is caused by the writer not using a capital letter to start a sentence.